Coronavirus as a possible cause of severe acute respiratory syndrome - Peiris, JSM (Lancet, 2003)
BACKGROUND: An outbreak of severe acute respiratory syndrome (SARS) has been reported in Hong Kong. We investigated the viral cause and clinical presentation among 50 patients. METHODS: We analysed case notes and microbiological findings for 50 patients with SARS, representing more than five separate epidemiologically linked transmission clusters. We defined the clinical presentation and risk factors associated with severe disease and investigated the causal agents by chest radiography and laboratory testing of nasopharyngeal aspirates and sera samples. We compared the laboratory findings with those submitted for microbiological investigation of other diseases from patients whose identity was masked. FINDINGS: Patients' age ranged from 23 to 74 years. Fever, chills, myalgia, and cough were the most frequent complaints. When compared with chest radiographic changes, respiratory symptoms and auscultatory findings were disproportionally mild. Patients who were household contacts of other infected people and had older age, lymphopenia, and liver dysfunction were associated with severe disease. A virus belonging to the family Coronaviridae was isolated from two patients. By use of serological and reverse-transcriptase PCR specific for this virus, 45 of 50 patients with SARS, but no controls, had evidence of infection with this virus. INTERPRETATION: A coronavirus was isolated from patients with SARS that might be the primary agent associated with this disease. Serological and molecular tests specific for the virus permitted a definitive laboratory diagnosis to be made and allowed further investigation to define whether other cofactors play a part in disease progression.